2008
DOI: 10.1016/j.micres.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the serine proteinase gene of Bacillus intermedius in Bacillus subtilis

Abstract: The gene encoding for Bacillus intermedius serine proteinase was cloned and the complete nucleotide sequence was determined. Gene expression was explored in the protease-deficient strain Bacillus subtilis AJ73 during different stages of growth. Catabolite repression involved in control of proteinase expression during transition state and onset of sporulation was not efficient at the late stationary phase. Salt stress leads to induction of serine proteinase production during B. subtilis AJ73(pCS9) post-exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…As for some other species of Bacillus (Sharipova et al, 2008), the extracellular proteolytic activities in B. pumilus BA06 began during the early stationary growth phase (24 h), quickly reaching a peak in the mid-stationary growth phase (54 h), and then declining during the later stages of the stationary phase after 66 h (Figure 2A). When salt was added to the medium, proteolytic activities in the supernatant were extremely repressed (Figure 2A), which was also confirmed using the plate test ( Figure 2B).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As for some other species of Bacillus (Sharipova et al, 2008), the extracellular proteolytic activities in B. pumilus BA06 began during the early stationary growth phase (24 h), quickly reaching a peak in the mid-stationary growth phase (54 h), and then declining during the later stages of the stationary phase after 66 h (Figure 2A). When salt was added to the medium, proteolytic activities in the supernatant were extremely repressed (Figure 2A), which was also confirmed using the plate test ( Figure 2B).…”
Section: Discussionmentioning
confidence: 54%
“…Although the individual gene that contributed to the decrease in total extracellular proteolytic activity could not be identified, aprE was assumed to be the major gene because addition of salt into the medium led to considerable transcriptional repression of this gene (Figure 4). In addition, when the aprE gene with its own promoter from Bacillus intermedius was expressed in recombinant form in B. subtilis, extracellular proteolytic activity was induced by salt (Sharipova et al, 2008). Accordingly, the regulation of the aprE gene may differ somehow in various Bacillus species.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme preparations secreted at different growth stages do not have significant differences in enzymatic properties and substrate specificity. It was shown earlier that the subtilisin like proteinases secreted on different growth stages of the culture are the products of one gene with the expression con trolled by different mechanisms depending on the growth stage of bacilli [26,27]. The MALDI TOF analysis data and the results of the enzymatic proper ties study suggest that the B. pumilus enzymes secreted at the early and late stationary phase of the culture growth are expression products of one gene.…”
Section: Resultsmentioning
confidence: 86%
“…Dr. Y. Ferrary (Genencor, USA) kindly provided extracellular proteasedeficient strain B. subtilis JB 20-36 used as the plasmid host. Subtilisin-like proteinase B. intermedius gene with its own regulatory elements (Sharipova et al, 2008) was inserted into high-copy plasmid pCS9 (based on high-copy plasmid pCB22), which confers resistance to erythromycin (Sorokin and Khazak, 1990). Plasmid isolation was performed as described by Sambrook et al (1987).…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme appears in culture broth when the culture shows an overall slow-down of the growth kinetics, with maximum levels of the enzyme activity appearing at the 24th and 48th hour of growth (Balaban et al, 2004). Two fractions of enzyme produced by the bacteria in the early and late stationary phases were products of the single gene coding for B. intermedius extracellular serine subtilisin-like proteinase (AprBi), which was cloned and its complete nucleotide sequence was determined (GeneBank accession number AY754946) (Sharipova et al, 2008). It was found that two separate promoters induced during vegetative growth and sporulation control expression of proteinase gene.…”
Section: Introductionmentioning
confidence: 99%